The soul of an octopus : a surprising exploration into the wonder of consciousness - Montgomery, Sy (New York : Atria Paperback, 2016)
Presents an investigation into the emotional and physical world of the octopus.
Includes bibliographical references (pages 249-254) and index.
Keywords: Octopuses -- Behavior